Options for Types of Dental Health Personnel to Train for Ghana - Addo, ME (Ghana Medical Association, 2006)
OBJECTIVES: To explore the degree of agreement on issues surrounding the proposals for dental health personnel requirements among key oral health personalities who are central to determining policy on oral health personnel requirements for Ghana and to make recommendations to assist in the future development of dental health personnel requirements. DESIGN: A review of the literature, published documents and in-depth semi-structured interviews. SETTING: Dental health service in Ghana PARTICIPANTS: Key oral health personalities who are central to determining policy on oral health personnel requirements for Ghana RESULTS: There was a lack of consensus regarding key aspects of planning personnel requirements including the numbers and the kinds of professionals complementary to dentistry (PCDs) to develop, who should be responsible for their training, and which people to admit as trainees of PCDs. CONCLUSION: Greater discussion between the various agencies involved should take place to help ensure consensus on the overall policy objectives.